2021
DOI: 10.1016/j.nicl.2021.102615
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in striatal and amygdala response to emotional faces are related to symptom severity in social anxiety disorder

Abstract: Highlights Amygdala & striatal neural activity may underlie Social Anxiety Disorder (SAD). 80 individuals with SAD completed an emotion processing task during fMRI. Dorsal striatal & amygdala response to angry > happy related to illness severity. Activity in these regions may contribute to individual differences in SAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…This was not completely unexpected, given that we previously found no effect of age in males during the CS (Dulka et al, 2020). It has been suggested that a more appropriate time point to assess trace fear recall is SFP time point because this is when the animal should have learned to expect a shock and, thus, is a conditional response to the auditory cue (Gilmartin et al, 2012). During the SFP time point, 22-mo males froze less than 15-mo males (P = 0.02) and tended to freeze less than 3-mo males (P = 0.065).…”
Section: Resultssupporting
confidence: 52%
“…This was not completely unexpected, given that we previously found no effect of age in males during the CS (Dulka et al, 2020). It has been suggested that a more appropriate time point to assess trace fear recall is SFP time point because this is when the animal should have learned to expect a shock and, thus, is a conditional response to the auditory cue (Gilmartin et al, 2012). During the SFP time point, 22-mo males froze less than 15-mo males (P = 0.02) and tended to freeze less than 3-mo males (P = 0.065).…”
Section: Resultssupporting
confidence: 52%
“…However, these early FC changes were not associated with symptom changes at either early/during treatment or post-treatment, suggesting that other neural processes that are not captured by resting state measures may be more closely related to symptom change. For example, other studies have shown SAD symptoms were associated with brain activity in fear, reward, attention, or executive control circuitry (Crane, Chang, Kinney, & Klumpp, 2021; Mizzi, Pedersen, Lorenzetti, Heinrichs, & Labuschagne, 2021). Further studies could assess other downstream processes by evaluating pre- to post-treatment fMRI scan, which may be more closely related to symptom change.…”
Section: Discussionmentioning
confidence: 99%
“…Amygdala dysfunction is closely related to the occurrence of psychiatric diseases such as anxiety disorder [25][26][27][28]. Considerable evidence from animal models and humans has consistently shown the hyperactivation of amygdala neurons in response to stress exposure [29,30].…”
Section: Stress and Brainmentioning
confidence: 99%